(untitled) (Research, Society and Development, 2022)
Chlamydia trachomatis uroinfection has become, in recent years, the most prevalent sexually transmitted infection worldwide, affecting quality of life and causing severe morbidity and mortality. This infection is silent and can lead to long-term reproductive complications. This study evaluates the prevalence and distribution of C. trachomatis genotypes in sexual infections of women from Belém, Amazon, Brazil. A cross-sectional, descriptive and prospective study was carried out from March 2019 to February 2020. Endocervical secretions were collected and DNA was extracted from these samples for ompA gene amplification by nested PCR and agarose gel electrophoresis. Positive samples were genotyped by nucleotide sequencing. The strains were genotyped by comparing the sequences of this study with those deposited in a public database. The Odds Ratio test was used to assess the relationship between infection and the variables investigated. A total of 230 samples were included in the analyses, of which 11 were positive for infection with a mean age of 44.18 years. We found no significant association between infection rates and the different variables investigated. One of the sequenced samples was diagnosed as genotype D, while all other samples were genotype F. The low prevalence of C. trachomatis in the sexual infections recorded in the present study, and the prevalence of genotype F, may be related to the relatively advanced age of the participants. Our results reinforce the importance of preventing late sequelae in the female population of the Amazon.